A Case Report on Incidental Finding of an Odontome Attached with Primary Teeth - Muthukrishnan Kavitha; Gajula Shivasankarappa Prathima (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Odontomes are hamartomatous developmental malformations of dental tissues that cause disruptions in tooth eruption. In general, odontomes are more common in permanent dentition and are rarely found in primary dentition. This case report describes an odontome found incidentally attached to a primary tooth during routine radiographic diagnosis, and it emphasises the importance of early diagnosis and management of odontome to avoid future complications such as retained deciduous teeth and impaction of permanent teeth, malocclusion, and so on.